"Hetero‐Multifunctionalization" of Gallium Corroles: Facile Synthesis, Phosphorescence, Redox Tuning, and Photooxidative Catalytic Improvement. Issue 1 (12th December 2019) - Zhan, Xuan; Zini, Yael; Fridman, Natalia; Chen, Qiu‐Cheng; Churchill, David G.; Gross, Zeev
Abstract: Bromination of tris‐ and tetrakis‐trifluoromethylated gallium corroles (3CF3 −Ga and 4CF3 −Ga ) afforded tetrabrominated species 3CF3 −4Br−Ga and 4CF3 −4Br−Ga (yields: 20 % and 25 %) characterized by NMR, UV‐vis spectroscopy, and mass spectrometry. Red‐shifted absorption and emission bands were found; 3CF3 −4Br−Ga and 4CF3 −4Br−Ga displayed 5–12 nm shifts in their Soret bands and 8–17 nm shifts for their Q bands, compared to the respective nonbrominated species (3CF3 −Ga and 4CF3 −Ga ). The respective Φ F values were found to be 0.013 and 0.016; phosphorescence (lifetime=0.23 μs) was observed for 3CF3 −4Br−Ga (anaerobic, RT). The effect of tetrabromination on redox potentials (0.89 and 0.99 V) gave a 85 mV shift per Br atom in the reduction potential. 4CF3 −4Br−Ga allows for efficient catalytic photooxidative Br − to Br2 conversion compared to the β‐octa‐Br system (Br8 −Ga ) structurally characterized here. This "hetero‐multifunctionalization" approach, that is, is substitution with different sets of β‐substituents, can help optimize porphyrinoid properties. Abstract : Multipurpose : A synthetic and electrochemical study of a new conceptual class of corroles enables assessment of how β‐substitution better enables facile light‐assisted C−H activation processes such as the monobromination of phenol. The corroles feature three and four CF3 groups and four Br groups. This "hetero‐multifunctionalization" approach results in β‐substitution to help optimize porphyrinoid (photophysical) properties.